2014
DOI: 10.1155/2014/874648
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Video and Internet Gaming Addiction among Hong Kong Adolescents: A Pilot Study

Abstract: This pilot study investigated the patterns of video and internet gaming habits and the prevalence and correlates of gaming addiction in Hong Kong adolescents. A total of 503 students were recruited from two secondary schools. Addictive behaviors of video and internet gaming were assessed using the Game Addiction Scale. Risk factors for gaming addiction were examined using logistical regression. An overwhelming majority of the subjects (94%) reported using video or internet games, with one in six (15.6%) identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
146
1
18

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(180 citation statements)
references
References 37 publications
15
146
1
18
Order By: Relevance
“…The average percentage was 4.7% across all years, and a linear trendline of the data yielded slope m = −0.0137. No region or country appeared to have a remarkably different prevalence of IGD, though the highest rate was found in one study of high school students in Hong Kong (40) which used a less stringent cut-off score for determining IGD than other studies using that scale (. The majority of the studies were school-based.…”
Section: Resultsmentioning
confidence: 97%
“…The average percentage was 4.7% across all years, and a linear trendline of the data yielded slope m = −0.0137. No region or country appeared to have a remarkably different prevalence of IGD, though the highest rate was found in one study of high school students in Hong Kong (40) which used a less stringent cut-off score for determining IGD than other studies using that scale (. The majority of the studies were school-based.…”
Section: Resultsmentioning
confidence: 97%
“…A monothetic approach with a rating of 3 or above for all items was used to indicate gaming addiction (Lemmens et al, 2009) and a sum score of all items was used to indicate the extent of gaming addiction. The Chinese version of the GAS has been (Wang et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…It was found that neuroticism was negatively linked to PGB (Lehenbauer-Baum et al, 2015;Mehroof and Griffiths, 2010;Montag et al, 2011;Peters and Malesky, 2008). By contrast, Wang et al (2014) did not find an association between PGB and neuroticism.…”
Section: Pgb: Health-related Outcomesmentioning
confidence: 98%